Effectiveness of Open Worksheet Based on Problems on Skills of Science Process and Creative Thinking of Junior High School Students - Yusi Ardiyanti; Marsah Rahmawati Utami (LPPM Universitas Buana Perjungan Karawang, 2020)
The quality of education is a direct consequence of a change and development of learning at this time. To optimize learning that requires students to have science process skills and creative thinking (in accordance with 21st-century demands) it is necessary to develop more varied learning media. One way is to develop a problem-based open Worksheet that allows students to add information about a material systematically with reference to problem-based learning by covering several stages, including orienting students to problems, organizing students to learn, guiding individual investigations or group, develop and present data, and analyze and evaluate work results. That is expected to improve the skills mentioned above.